Evaluation of Non-Timber forest Products (NTFPs) In Bronze Casting Enterprise at Egun Street, Benin City, Edo state - C Kalu; EN Aigbobo (Journal of Applied Sciences and Environmental Management)
Evaluation of NTFPs input in bronze casting at Igun Street in Benin City was carried out with the use of measurement of inputs and questionnaires. Fifty percent sampling intensity was used to obtain 42 from the total population of 84 Bronze Casters. Data were analyzed with the use of descriptive statistics of frequency, percentages and inferential statistics using ANOVA. Results showed that there were significant differences (P<0.05) among the mean weight of the inputs. The results revealed that the seasonal price variation among the various inputs were 30, 22, 38 and 10% of the respondents for charcoal, beeswax, fuelwood and laterite respectively. The patronage levels of bronze users were always (34.51%), sometimes and once a while accounted for 45.22 and 20.24% respectively. Difficulties associated with sourcing of bronze casting inputs were expensive nature, scarcity, exportation, exotic nature and unstable supply which accounted for 34.43, 27.05, 34.43, 2.46 and 1.64% respectively. Also, 100% of the respondents were of the view that bronze was very difficult to source while 42.42% of them were of the opinion that beeswax was difficult to source. Charcoal, laterite and fuelwood were easy to sources expressed by 28.33, 27.51 and 9.10% of the respondents’ respectively. It is necessary to ensure sustainable management of NTFPs so as to guarantee their steady supply at reasonably low prices for bronze casting enterprise. @ JASEM